GLUCOCORTICOID-INDUCED UNMASKING OF CRANIAL DIABETES INSIPIDUS IN HYPOPHYSITIS: A CASE SERIES - Hamzah, Hamizah; Jiang, Chua Yi; Samsuddin, Syahrizan (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Hypophysitis is a rare inflammatory condition of the pituitary gland that can mimic other sellar masses. Glucocorticoid (GC) therapy remains the mainstay of treatment, but in some cases may unmask underlying posterior pituitary dysfunction such as cranial diabetes insipidus (DI). We report two distinct cases of hypophysitis in young women in which GC therapy revealed subclinical DI. CASE Case 1: A 25-year-old female presented with headache, visual blurring, and polyuria. Magnetic resonance imaging showed pituitary stalk thickening and a sellar mass suggestive of lymphocytic hypophysitis. Initial endocrine evaluation showed isolated hyperprolactinemia. Following high-dose GC therapy, she developed cranial DI confirmed biochemically and treated successfully with desmopressin. Follow-up MRI showed resolution of pituitary swelling. Case 2: A 22-year-old female with bullous skin lesions and chronic otorrhea was diagnosed with multisystem Langerhans Cell Histiocytosis (LCH). Chemotherapy with vinblastine and high-dose dexamethasone led to diabetic emergencies and the onset of cranial DI. Magnetic resonance imaging revealed infundibular involvement and empty sella. Desmopressin was initiated and doses of steroids and chemotherapy were tapered, resulting in clinical improvement. These cases highlight the phenomenon of GC-induced unmasking of DI in patients with hypophysitis. Inflammatory edema may initially obscure AVP dysfunction, which becomes apparent only after anti-inflammatory treatment. A high index of suspicion and close monitoring for polyuria following GC initiation are essential. Magnetic resonance imaging remains a valuable diagnostic tool, although radiological differentiation from other pituitary pathologies may be challenging. CONCLUSION Glucocorticoid therapy in hypophysitis can unmask subclinical cranial DI. Clinicians should be vigilant for evolving symptoms post-therapy. Early recognition and treatment of DI can significantly improve patient outcomes.